Sepsis-induced brain dysfunction. Issue 2 (February 2013) - Adam, Nicolas; Kandelman, Stanislas; Mantz, Jean; Chrétien, Fabrice; Sharshar, Tarek
Systemic infection is often revealed by or associated with brain dysfunction, which is characterized by alteration of consciousness, ranging from delirium to coma, seizure or focal neurological signs. Its pathophysiology involves an ischemic process, secondary to impairment of cerebral perfusion and its determinants and a neuroinflammatory process that includes endothelial activation, alteration of the blood–brain barrier and passage of neurotoxic mediators. Microcirculatory dysfunction is common to these two processes. This brain dysfunction is associated with increased mortality, morbidity and long-term cognitive disability. Its diagnosis relies essentially on neurological examination that can lead to specific investigations, including electrophysiological testing or neuroimaging. In practice, cerebrospinal fluid analysis is indisputably required when meningitis is suspected. Hepatic, uremic or respiratory encephalopathy, metabolic disturbances, drug overdose, sedative or opioid withdrawal, alcohol withdrawal delirium or Wernicke's encephalopathy are the main differential diagnoses. Currently, treatment consists mainly of controlling sepsis. The effects of insulin therapy and steroids need to be assessed. Various drugs acting on sepsis-induced blood–brain barrier dysfunction, brain oxidative stress and inflammation have been tested in septic animals but not yet in patients.